Impact of Training and Development on Financial Performance Case Study: Kosovo Enterprises - Arta Jashari, Enver Kutllovci (International Journal of Advanced Science and Technology, 2020)
Objective of this paper is to analyses the importance of training and developing practice and its impact on e financial performance of enterprises, respectively in return on investment-ROA and return on sale-ROS. We have study 319 enterprises form three main sectors of economy in Kosovo, where managers who were responsible to manage their employee in enterprise and where familiar with training and development practices answered the questionnaire. SPSS version 25.0 has been used for data analysis. Results of linear regression has shown that practice of training and development have a statistically significant impact on financial performance of enterprises. Based on the results of our study we suggest all the managers of human resources should pay attention of training and developing people as the most crucial capital of every enterprises.